Facilitating a Path to New Teacher Certification Amid the COVID-19 Pandemic: Unpacking States’ “Unchanged-New Flex” Guidelines - Slay, Laura E.; Riley, Jacqueline; Miller, Karyn (Frontiers in Education, 2020)
In the United States, amid the COVID-19 pandemic, schools and testing centers were forced to close on-site locations. With teacher candidates no longer able to complete clinical teaching or take certification exams in person, states created new recommendations for facilitating a pathway to teacher certification. Specifically, 19 states provided guidelines that allowed educator preparation programs (EPPs) flexibility in how teacher candidates completed existing certification requirements. By analyzing summaries of these states’ guidelines, themes of time, technology, flexibility/non-flexibility, and EPPs emerged. Using a comprehensive lens, this brief examines the role and implications of each of these themes in teacher certification during these unprecedented times.